The Effect of Using Wordwall Game Application Media on Economics Subjects on Student Learning Outcomes at SMA Negeri 2 Sanga Desa - Lestari, Ayu; Rachmawati, Diana Widh; Toyib, Muhammad (Data : Journal of Information Systems and Management, 2024)
In this study, the problems found in the field are that the teaching and learning process is not optimal because students experience a form of learning difficulties related to characteristic, personality and study habits or students who excel below their ability level (wordwaall game). By applying synectic learning media, it is expected to overcome or at least direct adjustments to the problems faced by students. This study aims to determine the learning interest of grade XI IPS 1 students in economic growth and development at SMA Negeri 2 Sanga Desa. The method used in this study is the experimental method. Based on the results of the study, the results of the student wordwall game test showed that the average student who experienced it was 85.66% in the experimental class. In the synectic model category, the average student activity is 46.66% and in the experimental class learning outcomes students have an average Student activeness is 46.66%. The overall increase that occurred in students after applying wordwall game media synectic learning in the experimental class had an average of 85.66% or in the creteria "Improving / influential". In the results of the hypothesis carried out by researchers using a simple regression formula, this study there is an influence of wordwall games on the interest of high school students in economics subjects at SMA Negeri 2 Sanga Desa on the material of economic growth and development obtained t_(count =) 7.277>t_(table=)1.697 which means Ha is accepted while Ho is rejected. This study has an influence on other factors. Thus, this study shows that there is an influence of wordwall games on high school students' interest in economics subjects at SMA Negeri 2 Sanga Desa.